2019
DOI: 10.1016/j.cemconres.2019.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization, and water uptake property of alkali-silica reaction products

Abstract: The reaction mechanism of alkali-silica reaction (ASR) is poorly understood due to the difficulties to directly characterize ASR products in concrete. In this study, ASR products with initial Ca/Si of 0.25 and (K+Na)/Si ratio 0.5 with different K/Na ratios are synthesized at 80 o C. The synthesized ASR products are characterized by different techniques, also the solution chemistry is analyzed and saturation indices are calculated. The results show that crystalline and nano-crystalline phases are formed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
65
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 111 publications
(81 citation statements)
references
References 46 publications
15
65
1
Order By: Relevance
“…The basal spacings of the other products, ranging from ~10 Å to 13.5 Å, seem inert to the moisture change. Lab-synthesis attempts indicated that their basal spacings are more determined by the synthesis temperature [19,26]. A compression as high as 2 GPa was also proven to result in a permanent basal spacing reduction of ~1 Å for ASR products with basal spacing around 12.2 Å from field concrete samples [31].…”
Section: Implications On Moisture Uptake By Asr Productmentioning
confidence: 99%
See 4 more Smart Citations
“…The basal spacings of the other products, ranging from ~10 Å to 13.5 Å, seem inert to the moisture change. Lab-synthesis attempts indicated that their basal spacings are more determined by the synthesis temperature [19,26]. A compression as high as 2 GPa was also proven to result in a permanent basal spacing reduction of ~1 Å for ASR products with basal spacing around 12.2 Å from field concrete samples [31].…”
Section: Implications On Moisture Uptake By Asr Productmentioning
confidence: 99%
“…Upon increasing R.H. to 97%, the 7.43 Å basal peak vanished while a new basal peak appeared 13 Å was often observed [17,19]. When the synthesis temperature dropped to 40 °C, a product with basal peaks at 10.8 Å and 8.9 Å was reported [26].…”
Section: Micro-xrd Of the Asr Productsmentioning
confidence: 99%
See 3 more Smart Citations